A cross sectional study to find out the duration of sleep and associated disorder among practicing advocates in Madurai district Tamil Nadu - Kannan, L.; P., Praveena (International Journal Of Community Medicine And Public Health, 2018)
Background: Sleep is a essential physiological process for attaining optimal health and wellbeing. Reduced duration of night sleep destructs the body’s ability to regulate stress hormones, raises the blood pressure and cardio vascular risk. The pressure of working in legal field creates stress, sleep deprivation and eventually hypertension. In view of above issues one of the main objectives of the study is to evaluate the relationship between duration of sleep and hypertension among practising advocates. Methods: A cross-sectional study was conducted in a sample of 300 practising advocates at Madurai district court for a period of 1 year by simple random sampling method. Results: Around 116 (38.67%) participants had less than 6 hours of night sleep and 184 (61.33%) participants had equal to or more than 6 hours of night sleep. Among participants with night sleep less than 6 hours, a majority of 97 (83.62%) were found to be hypertensives, whereas only 26 (14.13%) participants with night sleep equal to or more than 6 hours were hypertensives (p=0.00, odds ratio-31.02). Conclusions: The study explains that practising advocates with duration of night sleep less than 6 hours (83.62%) have a significant association with hypertension. Advocates experience work related depression, anxiety and stress. Therefore advocates are advised to well plan the work schedules, plan for short vacations and adopt basic life style modifications to prevent hypertension.